Teleophthalmology in Diabetic Retinopathy - Surendran, Thandalam Sundararajan (J Diabetes Sci Technol, 2014)
Over the past decade, there have been rapid strides in progress in the fields of telecommunication and medical imaging. There is growing evidence regarding use of teleophthalmology for screening of diabetic retinopathy. This article highlights some pertinent questions regarding use of telescreening for diabetic retinopathy. It deals with evidence regarding accuracy of diagnosis, patients satisfaction and cost-effectiveness. The American Telemedicine Association have given certain guidelines for teleheath practices for diabetic retinopathy. The article discusses regarding these guidelines. Finally, a working model for diabetic retinopathy screening through teleophthalmology has been described. Telescreening for diabetic retinopathy seems to be a cost-effective, accurate, and reliable method for screening for diabetic retinopathy. The American Telemedicine Association has set up guidelines for telescreening that should be adhered to provide quality screening services to people with diabetes.